1997
DOI: 10.1007/bf02382006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of geophagy soils in Kibale Forest, Uganda

Abstract: ABSTRACT. Four soil samples from the Kibale Forest, Uganda, representative of material regularly ingested by chimpanzees, were studied for their mineral, chemical, and geochemical composition. These geophagy soils have a high content of metahalloysite, a partially hydrated clay mineral that may act much like the pharmaceutical KaopectatC M. Among the elements that may act as a stimulus or stimuli for geophagy behavior, only iron is very high (total iron ranges from 60/o to 17%); other possibilities such as cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 16 publications
0
60
0
Order By: Relevance
“…animals at high altitude (>2500 m) may have an increased need for iron to replenish hemoglobin due to increased oxygen demand (Mahaney et al 1997), but that does not provide a plausible explanation for soil ingestion in this location.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…animals at high altitude (>2500 m) may have an increased need for iron to replenish hemoglobin due to increased oxygen demand (Mahaney et al 1997), but that does not provide a plausible explanation for soil ingestion in this location.…”
Section: Discussionmentioning
confidence: 91%
“…We did not detect elevated iron levels in Prickly Rose and therefore do not ascribe the increased iron levels in fecal pellets to this source. Mahaney et al (1997) found that 0.15-0.20% of iron in soils consumed by chimpanzees could be extracted with an acid of the same pH as that of the digestive tract, making it a bioavailable iron. Iron in soils could therefore be an important nutritional source for Snowshoe Hares.…”
Section: Discussionmentioning
confidence: 99%
“…Many pre-treatments of soil material also may affect results by destroying and preventing detection of potentially important clay minerals (Kabata-Pendias and Pendias 1992). Very few studies have selected a pH for extraction solutions that is similar to the pH of absorption sites in the digestive tract (e.g., Mahaney et al 1997). …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, mineral nutrients are usually sufficient in an animal's routine diet (Hladik and Gueguen, 1974;Gilardi et al, 1999); and, among primates, elements are similar between unconsumed soils and those consumed selectively and repeatedly (Izawa, 1993;Mahaney et al, 1995;Müller et al, 1997;Bolton et al, 1998). Furthermore, in soils consumed by chimpanzees, only Fe was present in high concentrations (range 6-17%; Mahaney et al, 1997). However, available Fe was only partially soluble in conditions modeling the chimpanzee stomach (oxalic acid at pH 2.0), indicating it was an improbable cue.…”
mentioning
confidence: 97%
“…Accordingly, Kaopectate ® and Smecta ® are common commercial products featuring, respectively, kaolinite and smectite, clays that assuage diarrhoea in monkeys and humans (Beck et al, 1977;Leber, 1988;Guarino et al, 2002). Compellingly, humans report consuming soil expressly to relieve diarrhoea, and kaolinite is usually, but not always, the principle clay fraction ingested by humans and nonhuman primates (Vermeer and Ferrell, 1985;Aufreiter et al, 1997;Mahaney et al, 1997Mahaney et al, , 2000Knezevich, 1998). Of course, both adsorptive functions are not mutually exclusive.…”
mentioning
confidence: 99%